Suffragism and italianità : political and literary discourses of women's citizenship in Italy, 1900-1923 - Delaney, Emer (Trinity College (Dublin, Ireland). Italian Department, 2014)
The present research sets out to trace distinctive patterns of language use around the issue of women’s suffrage in early-twentieth-century Liberal Italy. In particular, the question of how women’s identities were constructed in suffrage-related discourse is addressed.
Keywords: Languages, Literatures & Cultural Studies, Ph.D.; Ph.D. Trinity College Dublin